Covid-19 Outbreak and its Microbiological Prospective - Amgain, Kapil; Neupane, Sujana (Journal of Karnali Academy of Health Sciences, 2020)
Covid-19 which started as an outbreak from Wuhan, China in December, 2019 was declared as Public Health Emergency in 30th January 2020, and pandemic on 11th March, 2020 by World Health Organization (WHO). Many microbiologists and scientists are conducting research on its structure, virulence, prevention and management to get the answers to some pertinent questions related to Covid-19. Here is an interview with one of the senior microbiologists of Nepal, Prof. Dr. Bharat Mani Pokhrel started his career from Institute of Medicine, Tribhuvan University. Dr. Pokhrel is Post Doc. Fulbright Scholar in Microbiology and one of the pioneer microbiologist in Nepal. Professor Pokhrel is an Academician of Nepal Academy of Science & Technology (NAST). And retired from, Tribhuvan University Teaching Hospital after 39 years of his successful tenure. He has published more than 150 research articles in national as well as international scientific medical journals. Currently Professor Pokhrel is an Academic advisor to KAHS, Jumla.